2008
DOI: 10.1103/physrevb.78.085115
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of energy transfer in a light-harvesting system under quantum coherence

Abstract: We investigate the role of quantum coherence in the efficiency of excitation transfer in a ring-hub arrangement of interacting two-level systems, mimicking a light-harvesting antenna connected to a reaction center as it is found in natural photosynthetic systems. By using a quantum jump approach, we demonstrate that in the presence of quantum coherent energy transfer and energetic disorder, the efficiency of excitation transfer from the antenna to the reaction center depends intimately on the quantum superposi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
376
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(382 citation statements)
references
References 34 publications
6
376
0
Order By: Relevance
“…Small deviations come from J23 not being so small. This model presents the advantage, as compared to the previous one, of enabling a direct analysis in the local site basis, which lets us avoid the sink approximation (13). The equations (8) fit this model if we assume that the sum of k's restricts to just one mode.…”
Section: Appendix B: Non-markovian Analysis Of a Three Site Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Small deviations come from J23 not being so small. This model presents the advantage, as compared to the previous one, of enabling a direct analysis in the local site basis, which lets us avoid the sink approximation (13). The equations (8) fit this model if we assume that the sum of k's restricts to just one mode.…”
Section: Appendix B: Non-markovian Analysis Of a Three Site Networkmentioning
confidence: 99%
“…In the case of the Fenna-MatthewsOlson (FMO) complex, these coherences can persist on picosecond timescales in cryogenic conditions and are still observable at room temperatures [2,8]. Several phenomenological theories have subsequently shown that there is an optimal mixture of coherent inter-pigment energy transport and stochastic environmental noise that may lead to faster and higher-yield energy delivery in PPC architectures, suggesting that quantum effects may underpin their efficient function [9][10][11][12][13][14][15]. Microscopic investigations have also recently shown the key role of both discrete and continuous environmental fluctuation spectra in stabilising the long-lasting coherences observed in spectroscopy as well as facilitating efficient transport [16][17][18][19][20].…”
mentioning
confidence: 99%
“…The functional principles displayed by the chromatophore and prevalent also in other photosynthetic systems include efficient excitonic coupling between components (Hu et al, 1997van Grondelle and Novoderezhkin, 2006b;Olaya-Castro et al, 2008;Sener et al, 2011), the utilization of quantum coherence (Ishizaki and Fleming, 2009a;Strümpfer et al, 2012), photoprotection by carotenoids (Damjanovic´et al, 1999), accommodation of thermal fluctuations, studied through experimental (Visscher et al, 1989;van Grondelle et al, 1994;Pullerits et al, 1994;Gobets et al, 2001;Janusonis et al, 2008;Freiberg et al, 2009) as well as theoretical (Damjanovic´et al, 2002;Ishizaki and Fleming, 2009b; van Grondelle eLife digest Photosynthesis, or the conversion of light energy into chemical energy, is a process that powers almost all life on Earth. Plants and certain bacteria share similar processes to perform photosynthesis, though the purple bacterium Rhodobacter sphaeroides uses a photosynthetic system that is much less complex than that in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of these new finds has been felt well beyond the photosynthesis research community, and the quantum properties of energy transfer in biological systems have attracted researches from seemingly unrelated fields of quantum computation and quantum information science. Questions about the relevance of quantum effects in natural light harvesting have led researches to study quantum entanglement [21][22][23], various aspects of the environmental assistance in quantum transport and optimality of transport processes [24][25][26][27][28]. Meanwhile, measurement of electronic coherence have found utility in determining structure-related properties of photosynthetic systems.…”
Section: Introductionmentioning
confidence: 99%